An application of reverse osmosis process on effluent treatment for the rubber industry - Ralengole, Galebone (My University, 2009)
The methods used to remove potassium sulphate (K2S04) and other impurities contained within Karbochem finishing plant effluent were investigated. Reverse osmosis was explored for this application. The study was conducted in two steps. The first step focuses mainly on the effluent treatment using BW30 flatsheet as well as BW30-2540 spiral-wound reverse osmosis membranes for the rejection of potassium and sulphate ions. The membranes were supplied by Filmtec. The second step reveals the possible use of potassium sulphate obtained from the brine stream in the fertiliser and fertigation industry by a literature search. Reverse osmosis study was conducted on a laboratory scale unit using flat sheet membranes and also on a pilot plant scale using spiral wound membrane modules. The tests were conducted at a feed pressure of 20 bar(g) with the membrane rejections being 98% and 99.1% on flat sheet membrane, and 96.9% and 99.4% on spiral wound membrane for potassium and sulphates respectively. The results show that both membranes have completely desalinated. Significant reduction in the concentrations of all problematic quality parameters, especially of potassium and the sulphate ions was noted. Granular activated carbon (GAC) bed treatment was recommended for pretreatment of the effluent prior to exposure of the membrane to avoid organic fouling of the membrane. GAC treatment was tested to illustrate its effectiveness to adsorb the COD's.
M. Tech., (Chemical Engineering, Department of Chemical Engineering, Faculty of Engineering and Technology Vaal University of Technology|
Keywords: Potassium sulphate; Karbochem finishing plant effluent; Reverse osmosis; Fertilser industry; Granular activated carbon bed treatment; Rubber industry; 628.164; Water reuse.; Rubber industry and trade.; Reverse osmosis process (Water purification)